Significance of comment, deletion and appreciation in letters The Holy Quran as an example (Journal of the College of Basic Education, 2023)
Quranic studies have presented a lot of general and specific topics thatThe Arab library enriched different types of science in language, society, law and even science.purely what is in medicine and cosmic phenomena in physics and astronomy and there is no room in this hasteIn order to talk about it in detail and mention its many evidences, and with regard to our topic, the field of research, I studiedAll fields and specializations of the language of morphology, sound and grammar. As for the Quranic rhetoric, my father hadObaid Muammar bin